2012
DOI: 10.1002/cne.23064
|View full text |Cite
|
Sign up to set email alerts
|

Connections of the lateral hypothalamic area juxtadorsomedial region in the male rat

Abstract: The connections of the lateral hypothalamic area juxtadorsomedial region (LHAjd) were investigated in a series of pathway-tracing experiments involving iontophoretic co-injection of the tracers Phaseolus vulgaris-leucoagglutinin (PHA-L; for outputs) and cholera toxin B subunit (CTB; for inputs). Results revealed that the LHAjd has connections with some 318 distinct gray matter regions encompassing all four subsystems—motor, sensory, cognitive, and behavioral state—included in a basic structure–function network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
95
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(110 citation statements)
references
References 209 publications
(303 reference statements)
15
95
0
Order By: Relevance
“…Because we highlight the hypothalamus-Acb axis regarding MCH participation, the present findings can also reinforce the structural basis of the role for MCH in modulating the reward value attributed to cocaine, which was claimed by Chung et al (2009). Swanson (1987) and Hahn and Swanson (2012) proposed the division of the hypothalamus into neuroendocrine [periventricular], neurovegetative [medial] and associative/limbic [lateral] zones, each one influencing the motivated behavior in a particular and different way. Our findings provide anatomical/hodological evidence that AcbSh is involved in these three different aspects of motivated behavior regarding the participation of MCH.…”
Section: Functional Considerationssupporting
confidence: 76%
“…Because we highlight the hypothalamus-Acb axis regarding MCH participation, the present findings can also reinforce the structural basis of the role for MCH in modulating the reward value attributed to cocaine, which was claimed by Chung et al (2009). Swanson (1987) and Hahn and Swanson (2012) proposed the division of the hypothalamus into neuroendocrine [periventricular], neurovegetative [medial] and associative/limbic [lateral] zones, each one influencing the motivated behavior in a particular and different way. Our findings provide anatomical/hodological evidence that AcbSh is involved in these three different aspects of motivated behavior regarding the participation of MCH.…”
Section: Functional Considerationssupporting
confidence: 76%
“…However, in order to be able to sample reliably from the same regions across different brains, we defined three larger areas for analysis: perifornical, lateral, and ventral (Figure 2). The perifornical area (LHApf) (Levels 27-30, −2.00 to −3.25 mm) we defined here contained the juxtadorsomedial and suprafornical nuclei (Swanson, 2004; Hahn and Swanson, 2010, 2012). The lateral area (LHAl) (Levels 27-30, −2.00 to −3.25 mm) included the region lateral to the LHApf, and was bordered dorsally by a line that matches the dorsal end of the third ventricle and ventrally by the ventral edge of the fornix.…”
Section: Methodsmentioning
confidence: 99%
“…13) (Cechetto and Saper, 1988). Recent studies using anterograde tracing with PHA-L have attempted to dissect the projections from different lateral hypothalamic fields (e.g., the region just lateral to the paraventricular nucleus vs. that just dorsal to the fornix, and that just lateral to the dorsomedial nucleus) (Hahn and Swanson, 2010;Hahn and Swanson, 2012). These studies have found some evidence for topographic organization, confirming that the long descending projections to the autonomic sites in the pons and medulla appear to come from the tuberal region.…”
Section: Lateral Hypothalamic Areamentioning
confidence: 99%